Life Domains and Dating Violence Among Latino Youth: A Partial Test of Agnew's Integrated General Theory. (September 2021) - Zavala, Egbert; Muniz, Caitlyn N.
In 2005, Agnew presented a new theoretical framework for understanding crime and delinquency. To date, this theory has not been thoroughly tested among various populations and types of crime. To address this gap in the research, the present study analyzes data gathered from the Dating Violence Among Latino Adolescents Study, providing a partial test of Agnew's integrated general theory to determine its applicability to dating violence perpetration among Latino youth. Results from 669 Latino respondents showed that the theory's constructs are modestly associated with perpetrating dating violence among this study population. Concepts depicting self (anger) and peer (peer bullying) domains are associated with the dependent variable, while school (school performance) and family (family support) domains were found to be nonsignificant. Among control and demographic variables, age, sex, depression, anxiety, and past dating victimization were also significant, while enculturation was nonsignificant. Overall, results are indicative of partial support for the theory. Prevention and intervention strategies based on the study's findings targeted at reducing dating violence perpetration, such as recognizing signs of anger and reducing peer bullying victimization, are discussed.